NEW FACTS AND NEW EVIDENCE AS A BASIS FOR REOPENING CRIMINAL PROCEEDINGS - Ilić, Ivan B (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
Reopening of criminal proceedings is a legal way to examine the factual basis of a final judgment based on an extraordinary legal remedy. The examination of the factual basis of the final judgment is initiated by the submission of a request for reopening the proceedings. This extraordinary remedy was established with the aim of establishing the truth in the criminal procedure, and is contrary to the principle of ne bis in idem. The factual deficiences of a final judgment are remedied on the basis of new, or newly discovered facts, or evidence that arose after the finality of the judgment. Article 473 of the Criminal Procedure Code envisages the reasons for repeating the criminal proceedings. They can be grouped in various ways. One of the groups includes new facts and evidence, as a reason for repeating the proceedings. First of all, there are new facts and evidence that per se or in concert with other evidence may lead to a acquittal, or a repudiation judgment, or condemnation on a more lenient law (Article 473, para. 1, point 3 of the CPC). This group also includes new facts and evidence indicating that the defendant did not commit any of the actions of an extended criminal offense, or other offence, which includes several acts (Article 473, para. 1, point 5 of the CPC). The new facts and evidence, which would lead to a milder criminal sanction, are another reason that we classify in this group (Article 473, para. 1, point 6 of the CPC). Finally, there are also new facts and evidence that the defendant was not properly summoned for the main trial, which was held in his/her absence (Article 473, para. 1, point 7 of the CPC). Compared with the procedural laws of other states, our CPC provides a lot of grounds for reopening the procedure. In this way, an adequate legislative framework was provided for making a more favorable decision on the defendant in the procedure for this extraordinary legal remedy. Although the envisaged grounds for reopening criminal proceedings constitute a satisfactory basis for instituting proceedings under this extraordinary legal remedy, further clarification de lege ferenda is necessary. Our procedural law prohibits reopening criminal procedure to the detriment of the defendant. The prescription of the repetition of the proceedings to the detriment of the defendant, in some future revision of the procedural code, would not be contrary to the Constitution, except that, in the case of the merits of the request, the outcome would have been the adoption of the declaratory judgment. There are also interpretations that the Constitution allows both the conduct of the proceedings and rendering the decision at the detriment of the defendant in the procedure for extraordinary legal remedies. In that case, in the future, a reduced number of grounds for reopening the proceedings should be envisaged at the detriment of the defendant.